2007
DOI: 10.1140/epjb/e2007-00114-7
|View full text |Cite
|
Sign up to set email alerts
|

Excitable scale free networks

Abstract: When a simple excitable system is continuously stimulated by a Poissonian external source, the response function (mean activity versus stimulus rate) generally shows a linear saturating shape. This is experimentally verified in some classes of sensory neurons, which accordingly present a small dynamic range (defined as the interval of stimulus intensity which can be appropriately coded by the mean activity of the excitable element), usually about one or two decades only. The brain, on the other hand, can handl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
1
33
0
1
Order By: Relevance
“…This signal compression property, or enhancement of dynamic range, is a general property of excitable media and has proven very robust against variations in the topology of the medium and the level of modeling, from cellular automata to compartmental conductance-based models [21][22][23][24][25][26][27][28][29][30][31][32][33]. Furthermore, the idea that dynamic range can be enhanced in neuronal excitable media has received support from experiments in very different setups [34,35], which again suggests that the phenomenon is robust.…”
Section: Introductionmentioning
confidence: 99%
“…This signal compression property, or enhancement of dynamic range, is a general property of excitable media and has proven very robust against variations in the topology of the medium and the level of modeling, from cellular automata to compartmental conductance-based models [21][22][23][24][25][26][27][28][29][30][31][32][33]. Furthermore, the idea that dynamic range can be enhanced in neuronal excitable media has received support from experiments in very different setups [34,35], which again suggests that the phenomenon is robust.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that such networks have their sensitivity and dynamic range maximized at the critical point of a nonequilibrium phase transition [3]. Later, models on other diverse networks, including those with scale-free, degree-correlated, and assortative topologies, were discussed [17,18]. More recently, a general theoretical approach to study the effects of network topology on dynamic range was presented by Larremore, Shew, and Restrepo [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to process stimulus intensities across several orders of magnitude is maximal at the point where stimuli are amplified as much as possible, but not so much as to engage the network in stable self-sustained activity. That result has been generalized in a number of models, including excitable networks with scale-free topology [6,7], with signal integration where discontinuous transitions are possible [39], or with an interplay between excitatory and inhibitory model neurons [40]. In fact, the mechanism does not even need to involve excitable waves, appearing also in a model of olfactory processing where a disinhibition transition involving inhibitory units takes place [41].…”
Section: Nonlinear Collective Response and Maximal Dynamic Range At Cmentioning
confidence: 96%
“…It is important to emphasize that some of the simplifications employed in this model cannot be taken for granted. The hand-waving argument for = 1 being the critical value of the coupling parameter, for instance, fails if the topology of the network is more structured than a simple Erdős-Rényi random graph [6,7]. The extension of the above results to more general topologies was put forward by Restrepo and collaborators [8,9].…”
Section: Phase Transition In a Simple Modelmentioning
confidence: 99%